Exposição a material particulado em um canteiro de obra da construção civil e sua associação com marcadores inflamatórios sanguíneos - Santos, Isis Moreira (2018)
Civil construction is known as one of the barriers to sustainable development. Among the impacts that the civil construction causes, the emission of particulate matter in the atmosphere stands out, which are responsible for air pollution and several health diseases. In this sense, the objective of this work was to evaluate the exposure of workers to particulate matter (PM) and its elemental composition, from a construction site, and also to analyze its possible associations with blood inflammatory markers. It is a longitudinal study of repeated measurements with the same group, but at different moments: with and without exposure to the PM present in the environment of construction sites. The sample consisted of 41 volunteers male workers from Londrina civil construction. Samples of 15 mL of blood from volunteers were collected at both moments. A questionnaire was also applied to the knowledge of the characteristics of the work and sample group, and of possible effects of exposure to PM. In the blood samples, several health parameters were determined with emphasis on inflammatory markers, interleukins 1B, 2, 4, 5, 6, 8 and 10, and granulocyte macrophage colony stimulating factor (GM-CSF) interferon gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α). In order to evaluate the MP exposure, measurements were made inside work environment for 8 consecutive hours on workdays, from May 08 to 19, 2017. Were measured the particles number concentrations (PNC) for cut off diameters of 0.3, 0.5, 1 and 2.5 μm, inhalable particulate matter (PM10) and its elemental composition by collecting it in PTFE filters. The elemental analysis of PM10 was performed by x-ray fluorescence and Black Carbon equivalent (BCe) by light reflectance. The mean PM10 concentration in the period was 120.5 ± 113.5 μg m-3. The mean values for PNC0.3, PNC0.5, PNC1, PNC2.5 were 92,447, 34,675, 17,595 and 7,106 particles L-1, respectively. The highest average concentrations were found for the Ca, Si and Fe elements, which were associated with cement, mortar and sand, which are consumed in a large scale in civil construction, thus characterizing the working environment. The mean BCe concentration was 4.5 μg m-3 representing 3.7% of the mass of PM10, which was mainly associated with diesel vehicles that have access to the construction site. The results of the analysis of the markers indicated that the cytokines analyzed were sensitive to the differences in exposure, but were in average higher at the time without exposure to the PM from construction environment (vacations). This result may possibly be explained by higher exposure to interferents agents during this holiday period, due to the greater frequency of atypical activities performed during this period, which possibly resulted in higher exposure, since they used masks in the work. However, future analyzes are necessary to get conclusive results.